2022
DOI: 10.1002/ptr.7625
|View full text |Cite
|
Sign up to set email alerts
|

Piperine attenuates the inflammation, oxidative stress, and pyroptosis to facilitate recovery from spinal cord injury via autophagy enhancement

Abstract: Spinal cord injury (SCI) is a serious injury that can lead to irreversible motor dysfunction. Due to its complicated pathogenic mechanism, there are no effective drug treatments. Piperine, a natural active alkaloid extracted from black pepper, has been reported to influence neurogenesis and exert a neuroprotective effect in traumatic brain injury. The aim of this study was to investigate the therapeutic effect of piperine in an SCI model. SCI was induced in mice by clamping the spinal cord with a vascular clip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Recent studies have shown that oxidative stress is involved in a series of neurological diseases, including cerebral ischemia, SCI, and Alzheimer’s disease. Many studies have confirmed that excessive ROS can exacerbate SCI . Excessive ROS production can cause severe damage to proteins and DNA in spinal cord tissue, ultimately leading to increased inflammation and neuronal cell death. , ROS, GSH, SOD, and MDA are widely used as markers of oxidative stress after SCI. , In the present study, both in vitro and in vivo experiments showed that SeNPs-Met-MVs could be a key regulator of neuroprotection in response to oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
“…Recent studies have shown that oxidative stress is involved in a series of neurological diseases, including cerebral ischemia, SCI, and Alzheimer’s disease. Many studies have confirmed that excessive ROS can exacerbate SCI . Excessive ROS production can cause severe damage to proteins and DNA in spinal cord tissue, ultimately leading to increased inflammation and neuronal cell death. , ROS, GSH, SOD, and MDA are widely used as markers of oxidative stress after SCI. , In the present study, both in vitro and in vivo experiments showed that SeNPs-Met-MVs could be a key regulator of neuroprotection in response to oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have found that some CRMs, such as resveratrol and aspirin, inhibit oxidative stress and reduce ROS levels 78 , 79 . Activation of the antioxidative stress mechanism inhibits pyroptosis and necroptosis of neurocytes by regulating autophagy 80 . Whether 3,4-DC promotes autophagy and inhibits pyroptosis and necroptosis by inhibiting oxidative stress remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that increased autophagy can reduce inflammation and pyroptosis ( 107 , 108 ). In the context of alleviating SCI, betulinic acid (BA) and piperine have been found to activate autophagy, leading to a decrease in ROS formation and NLRP3/GSDMD-mediated pyroptosis ( 75 , 109 ). Specifically, BA activates macroautophagy through the AMPK-mTOR-TFEB pathway, which in turn reduces ROS accumulation by enhancing mitophagy, thereby inhibiting pyroptosis ( 75 ).…”
Section: Ros In Pyroptosismentioning
confidence: 99%